The short- and medium-term impacts of Sure Start on educational outcomes - Pedro Carneiro; Sarah Cattan; Nick Ridpath (Institute for Fiscal Studies (IFS), 2024)
This report presents evidence of the short- and medium-term impacts of the programme on educational outcomes. Using a robust evaluation methodology and administrative education data covering 15 cohorts of children, we measure the impact of having had access to a Sure Start centre between ages 0 and 5 on school outcomes, including academic achievement and special educational needs. We estimate how these effects vary across different backgrounds, and shed some light onto the mechanisms that might have made Sure Start more or less effective.
Keywords: 330; Education and skills; Childcare and early years; Early childhood development; Education; Human capital